Implantable cardioverter-defibrillator therapy after resuscitation from cardiac arrest in vasospastic angina. (14th October 2021) - Tateishi, K; Kondo, Y; Saito, Y; Kitahara, H; Kobayashi, Y
Abstract: Background: Patients with vasospastic angina (VSA) who are resuscitated from sudden cardiac arrest (SCA) are at high risk of recurrent cardiovascular events. However, there are no recommendations for implantable cardioverter-defibrillator (ICD) therapy in the VSA and SCA patient guidelines. Purpose: This study investigated the prognostic impact of ICD therapy on patients with VSA and SCA. Methods: The present multi-center registry included 280 patients who were resuscitated from SCA and received ICD implantation as secondary prophylaxis. The patients were divided into two groups according to the presence of VSA. The primary endpoint was a composite of all-cause death and appropriate ICD therapy, including appropriate anti-tachycardia pacing and shock for recurrent ventricular arrhythmias. Results: Of 280 patients, 51 (18%) had VSA. Among those without VSA, ischemic cardiomyopathy was the leading cause of SCA (38%), followed by non-ischemic cardiomyopathies and Brugada syndrome (Table 1). During the median follow-up period of 3.8 years, 23 (8%) patients died, and 72 (26%) underwent appropriate ICD therapy. The incidence of the primary endpoint was not significantly different between patients with and without VSA (24% vs 33%, p=0.19). Further, the incidence of the primary endpoint was not significantly different among the etiologies (Figure 1) Conclusions: In a cohort of patients who underwent ICD implantation as secondary prophylaxis, long-term clinical outcomes were comparable between those with VSA and those with other cardiac diseases after SCA. The results suggest that ICD therapy may be considered in patients with VSA and those with other etiologies after resuscitation from SCA. Funding Acknowledgement: Type of funding sources: None.